2007
DOI: 10.1074/jbc.m702212200
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Class I-ERp57-Tapasin Interactions within the Peptide-loading Complex

Abstract: The endoplasmic reticulum-located multimolecular peptideloading complex functions to load optimal peptides onto major histocompatibility complex (MHC) class I molecules for presentation to CD8 ؉ T lymphocytes. Two oxidoreductases, ERp57 and protein-disulfide isomerase, are known to be components of the peptide-loading complex. Within the peptide-loading complex ERp57 is normally found disulfide-linked to tapasin, through one of its two thioredoxin-like redox motifs. We describe here a novel trimeric complex th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 32 publications
3
40
1
Order By: Relevance
“…1D, lanes 6 and 7). These results confirm previously published results that demonstrated a mixed disulfide between heavy chain, ERp57, and tapasin (20) and show for the first time that a disulfide can form between heavy chain and tapasin. It should be stressed that the formation of disulfide bonds in these experiments could well be a result of the prevailing redox conditions within the in vitro translation system (see "Discussion").…”
Section: Mhc Class I Heavy Chain Forms Mixed Disulfides With Componensupporting
confidence: 93%
See 2 more Smart Citations
“…1D, lanes 6 and 7). These results confirm previously published results that demonstrated a mixed disulfide between heavy chain, ERp57, and tapasin (20) and show for the first time that a disulfide can form between heavy chain and tapasin. It should be stressed that the formation of disulfide bonds in these experiments could well be a result of the prevailing redox conditions within the in vitro translation system (see "Discussion").…”
Section: Mhc Class I Heavy Chain Forms Mixed Disulfides With Componensupporting
confidence: 93%
“…A ternary complex between ERp57, tapasin, and heavy chain has previously been identified that was suggested to include a mixed disulfide between ERp57 and heavy chain via the ␣2 cysteine residues (20). To determine whether the ternary complex we observed in our experimental system also contains a mixed disulfide between ERp57 and the ␣2 cysteines of heavy chain, we used the approach that maximized the formation of this complex.…”
Section: Mhc Class I Heavy Chain Forms Mixed Disulfides With Componenmentioning
confidence: 94%
See 1 more Smart Citation
“…After initial interaction with the lectin-like chaperone calnexin, MHC class I heavy chain-␤ 2 -microglobulin (␤ 2 m) heterodimers are incorporated into the peptide-loading complex (PLC), a multimolecular unit of ER proteins that promotes optimal peptide loading into MHC class I molecules (Hammerling et al, 1998;Pamer and Cresswell, 1998;Elliott and Williams, 2005). The PLC contains calreticulin, tapasin, transporters associated with antigen processing (TAP) and two thioldependent oxidoreductases, ERp57 and protein disulfide isomerase (PDI) (Garbi et al, 2005;Park et al, 2006;Santos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…After initial interaction with the lectin-like chaperone calnexin, MHC class I heavy chain-␤ 2 -microglobulin (␤ 2 m) heterodimers are incorporated into the peptide-loading complex (PLC), a multimolecular unit of ER proteins that promotes optimal peptide loading into MHC class I molecules (Hammerling et al, 1998;Pamer and Cresswell, 1998;Elliott and Williams, 2005). The PLC contains calreticulin, tapasin, transporters associated with antigen processing (TAP) and two thioldependent oxidoreductases, ERp57 and protein disulfide isomerase (PDI) (Garbi et al, 2005;Park et al, 2006;Santos et al, 2007).Several functions have been proposed for tapasin in facilitating optimal peptide loading and optimization of the peptide cargo (Grandea and Van Kaer, 2001;Purcell et al, 2001;Momburg and Tan, 2002). Tapasin bridges heavy chain-␤ 2 m heterodimers to TAP (Sadasivan et al, 1996) and thus provides physical proximity between MHC class I molecules and TAP.…”
mentioning
confidence: 99%